A walkthrough journey with the computer in ESL classroom - Abdul Razak, Noor Zainab (Penerbit UTM Press, 2009)
Educators have always been creative in their attempts to apply new technologies in their methods. In the past, there have been many examples of prominent uses of the language laboratory, radio cassettes, videos and televisions. However, in this 21 st century, the computer technology provides a new learning environment with wealth pedagogic possibilities. The widespread use of technology has create new opportunities for language learning. It is important for language teachers to understand the new possibilities in teaching and students’ interest so that they could help and encourage students to gain success in learning English language. Thus, this paper intends to explore the benefits of computers in language learning and teaching. The benefits and limitations of computers in a language learning classroom will be discussed as computer is the main medium where huge amounts of information including the Internet facilities can be obtained. The advent of the Internet and the widespread use of technology has create new opportunities for language learning. Hence, the computer can create a world where students can explore freely. The computer helps language teachers and learners to create and obtain useful materials in a short time. This paper therefore, also aims at providing a description of how computer with leverage wealth of content can be integrated in the ESL classroom. It intends to discuss how the computer fits into conventional language learning and teaching settings. Examples of the computer activities in the ESL classroom will be provided. The benefits and limitations of computers and the activities that can be carried out using the computer in language learning and teaching provide an insight into understanding the role computers in an ESL classroom better and how computers can complement conventional pedagogy.